Analisis Implementasi Kebijakan Pencantuman Peringatan Kesehatan dan Peringatan Kesehatan pada Kemasan Rokok - Diah Ekawati; Ede Surya Darmawan (Center for Health Policy and Management, 2019)
Analysis of Policy Implementation of Inclusion of Health Warnings and Health Information on Cigarette PacksBackground: The picture health warning has been applied for more than two years since June 24, 2014, but until now there has been no change in accordance with Minister of Health Decree No. 28 Year 2013. The National Survey of Implementation of Health Illustration Implementation Implementation in Indonesia in 2015 on cigarette industry compliance is known that the cigarette industry has not complied with the illustrated health warning. The Government's expectation with the Ministry of Health 28 could reduce the prevalence of smokers, but the 2016 Sirkernas data shows the prevalence of smoking is increasing. Objective: To dig deeper into the implementation of the policy of inclusion of health warnings and health information on cigarette packs for further input into the formulation of tobacco control strategies. Method: It is a descriptive study with qualitative analysis through in-depth interview and document review. Result: Outcome: Process aspects (communication, bureaucratic structure and disposition), actor aspect (commitment and relationship), content aspect (level, benefit and policy objectives) and context aspect (political culture and social economy) have interrelationship and influence each other in the implementation of inclusion health and health information on cigarette packaging. Conclusion: The implementation of health warning and health information on cigarette packing has been done and industry compliance level in listing PHW at retail level has reached 99.91%.Keywords: PHW, Cigarette, Tobacco, Policy implementationLatar Belakang: Peringatan kesehatan bergambar sudah diterapkan lebih dari dua tahun sejak 24 Juni 2014, akan tetapi sampai saat ini belum dilakukan pergantian sesuai dengan Permenkes No 28 Tahun 2013. Hasil Survei Nasional Penilaian Implementasi Peringatan Kesehatan Bergambar di Indonesia tahun 2015 terhadap kepatuhan industry rokok, diketahui bahwa industry rokok belum patuh terhadap peringatan kesehatan bergambar. Harapan Pemerintah dengan adanya Permenkes 28 dapat menurunkan prevalensi perokok akan tetapi data Sirkernas 2016 menunjukan prevalensi merokok semakin menningkat. Tujuan: Untuk menggali lebih dalam terhadap implementasi kebijakan pencantuman peringatan kesehatan dan informasi kesehatan pada kemasan rokok untuk selanjutnya dapat menjadi masukan dalam perumusan strategi pengendalian tembakau. Metode: Merupakan studi deskriptif dengan analisis kualitatif melalui wawancara mendalam dan telaah dokumen. Hasil: Aspek proses (komunikasi, struktur birokrasi dan disposisi), aspek aktor (komitmen dan hubungan), aspek konten (level, manfaat dan tujuan kebijakan) serta aspek konteks (budaya politik dan social ekonomi) memiliki keterkaitan dan saling mempengaruhi dalam pelaksanaan pencantuman peringatan kesehatan dan informasi kesehatan pada kemasan rokok. Kesimpulan: Bahwa pelaksanaan pencantuman peringatan kesehatan dan informasi kesehatan pada kemasan rokok sudah terlaksana dan tingkat kepatuhan industri dalam mencantumkan PHW ditingkat ritel telah mencapai 99.91%.Kata kunci: PHW, Rokok, Tembakau, Implementasi kebijakan